2020
DOI: 10.7573/dic.2020-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine-induced hyperpigmentation in a 14-year-old female with systemic lupus erythematosus

Abstract: Hydroxychloroquine (HCQ)-induced hyperpigmentation is uncommon but is increasingly recognized. To our knowledge, HCQ-induced hyperpigmentation has not been reported in the pediatric age group. Herein, we present the case of a 14-year-old girl with systemic lupus erythematosus, who developed hyperpigmentation on her shins and dorsum of the left foot, approximately 3 years after initiating treatment with HCQ. Physicians who treat children with HCQ for reasons such as rheumatologic disorders, dermatologic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Additionally, cardiovascular side effects associated with use of hydroxychloroquine were identified in SLE patients [ 76 ]. Hyperpigmentation also was reported in pedatric SLE patients under hydroxychloroquine [ 77 ].…”
Section: Personalized Therapeutic Approaches To Autoimmune Patients I...mentioning
confidence: 74%
“…Additionally, cardiovascular side effects associated with use of hydroxychloroquine were identified in SLE patients [ 76 ]. Hyperpigmentation also was reported in pedatric SLE patients under hydroxychloroquine [ 77 ].…”
Section: Personalized Therapeutic Approaches To Autoimmune Patients I...mentioning
confidence: 74%
“… 10 , 23 , 31 , 32 , 37 , 40 , 45 , 47 , 51 , 60 Cardiovascular adverse events were frequently reported in patients with SLE under HCQ or chloroquine (CQ) treatment, 26 and paediatric SLE patients might develop hyperpigmentation induced by HCQ. 34 …”
Section: Resultsmentioning
confidence: 99%
“…10,23,31,32,37,40,45,47,51,60 Cardiovascular adverse events were frequently reported in patients with SLE under HCQ or chloroquine (CQ) treatment, 26 and paediatric SLE patients might develop hyperpigmentation induced by HCQ. 34 The impact of COVID-19 pandemic on SLE patients Fifteen studies reported the impact of COVID-19 pandemic on SLE patients. During this lockdown period, SLE patients experienced supply shortages, missed the doses of drugs, underwent financial constraints and spent more money on healthcare.…”
Section: The Epidemiology Of Sle and Covid-19mentioning
confidence: 99%